Comparison of Post-Operative Outcomes of Blunt Dissection and Electrocautery Technique in Tonsillectomy; A Randomized Controlled Trail - Shahi Zeb, Babur Riaz, Nasir Riaz, Waseem Amin, Usama Naveed Cheema, Hafiz Muhammad Abdullah Tahir, Mirza Zeeshan Sikandar (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Tonsillectomy is most common procedure performed in ENT Practice. Various surgical techniques are used in this procedure, including blunt dissection, electrocautery, cryosurgery, ultrasonic removal, laser removal, monopolar and bipolar dissection. After tonsillectomy, morbidities associated are pain, fever and hemorrhage. Objective: In our study we compared the bipolar electrocautery dissection with cold steel dissection method. We compared compare post tonsillectomy morbidities in terms of, pain, fever, post-operative hemorrhage. Methodology: This study was a randomized controlled trial. All 100 patients scheduled for elective tonsillectomy was randomized to tonsillectomy with the hot technique (group-A) or the cold dissection technique (group-B). The randomization was performed by the use of a random number generator (Excel). Chi-square test/Fisher’s exact test was applied to compare hemorrhage and fever. Independent sample t-test was applied to compare pain in both study groups. Results: The mean age of patients in cold dissection was 23.26 ± 9.317 whereas in hot dissection group the mean age of the patients was 25.20 ± 8.013. At first day of procedure mild post-operative pain in 28 (28.0%) patients, moderate pain in 39(39.0%) patients and severe pain in 33(33.0%) patients was seen. In cold dissection group 19(38.0%) patients had mild, 26 (52.0%) had moderate and 5(10.0%) had severe postoperative pain while in hot dissection group 9(18.0%) patients developed mild, 13(26.0%) developed moderate and 28(56.0%) developed severe postoperative operative pain at day 1. Practical Implications: It will help in early and prompt management of patients of tonsils undergoing tonsillectomy with minimal invasion. Conclusion: In our study, the cold dissection was observed to be better in terms of low pain however; in terms of hemorrhage the hot dissection was found to be better. MeSH Words: Tonsillectomy, electrocautery, cold steel dissection, bleeding, pain, blood transfusion